Using art for children with development disabilities / Akehsan Dahlan, Rosilah Wahab and Erna Faryza Mohd Poot - Dahlan, Akehsan; Wahab, Rosilah; Mohd Poot, Erna Faryza (2023)
Children with developmental disabilities often struggle with basic life skills, communication, and social interaction. They may have conditions such as autism, attention deficit hyperactivity disorder (ADHD), and learning disorders. It is estimated that 1 in 6 children in the United States have a developmental disability. Early intervention and support from parents, educators, and healthcare providers can greatly improve outcomes for these children. However, there is still a significant lack of resources and support for families and individuals with developmental disabilities.